Contributions to the systematics of the genus Schizochilus - MacRobert, M; MacRobert, M (Department of Biological Sciences, 2017)
The genus Schizochilus, first described by Sonder in 1847 as an extra-tropical Southern African orchid, is based upon material collected by Ecklon and Zeyher in moist places in the Winterberg mountains. The main characters of the flower are a spurred, fleshy three-cleft lip; and free, erect sepals and petals, all three sepals being equal and the petals much smaller than the sepals. The type species, S. zeyheri Sond., is described as having a small number (2-3) of linear-oblong basal leaves and a spike of 16-20 small flowers. Sepals and petals are both noted as white, the sepals about 0,5 cm in length (2.5 lines) and marked with 3 rosy veins, the petals lanceolate and half the length of the sepals. The spur is "not much shorter than the labellum" and the ovary, "almost twice the length of the spur". The lip itself, obovate in outline, is covered with very small crystalline papillae, the lateral lobes being "somewhat shorter than title broader, obtuse intermediate lobe". There appears to be no mention of the basal tubercles or calli on the lip.